ETIOLOGICAL ASPECTS OF ISCHEMIC STROKE IN A YOUNG WOMAN: A CASE REPORT - Gulnara K. Rakhmattulaeva ,; Aziza Sh. Kadirova , (Central Asian Journal of Medicine, 2025)
One of the possible causes of early development of ischemic stroke is the inherited thrombophilia – a condition in which there is an increased tendency to form blood clots due to hereditary disorders of the hemostatic system. Thrombophilia refers to a group of disorders characterized by an increased predisposition to thrombus formation in blood vessels. Inherited thrombophilia is caused by genetic mutations that can impair to the normal regulation of blood coagulation. This article discusses the role of inherited thrombophilia in the development of ischemic stroke in a young woman – a clinical case, with a detailed description of the clinical features, diagnosis, and treatment of the patient.